مظاهر التعسف في استعمال الحق الإجرائي في الدعوى الجزائية - Samin, Sirwan Shukr; Saeed, Dr. Zana Rafiq (Journal of Legal and Political Studies, 2025)
The accused and the victim have rights that they exercise whether upon initiating the lawsuit, during its prosecution, or even upon its conclusion. They should not burden this right beyond its capacity and should use it in accordance with what the legislator has decided for them. Although it is common that the theory of abuse of rights is within the domain of private law, as a result of intellectual development, it has become clear that it can be applied in procedural criminal law. This study is an effort to demonstrate the manifestations of arbitrary use of the right in procedural actions carried out by procedural persons within the scope of criminal proceedings. Keywords: abuse, procedural right, procedural persons, criminal action.
Keywords: Keywords abuse; procedural right; procedural persons; criminal action